2002
DOI: 10.1046/j.1524-4725.2002.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Rhinophyma: Report of Eight Patients Treated with Electrosection

Abstract: Electrosection is as effective as laser treatments and less expensive. Although living in a laser era, electrosurgical remodeling of the nose is a good alternative for the treatment of rhinophyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 8 publications
1
32
0
1
Order By: Relevance
“…Most studies on surgical treatment of rhinophyma show good aesthetic results after very short follow-up periods [11,15,16,17]. However, the mid- and long-term efficacy of different modalities have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on surgical treatment of rhinophyma show good aesthetic results after very short follow-up periods [11,15,16,17]. However, the mid- and long-term efficacy of different modalities have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical reduction can be performed in two forms, either partial-thickness excision or full-thicness excision. In partial excision method the rhinophyma is shaved off tangentially and the residual deep pilosebaceous appendages produce re-epitelization [1,19,21]. At the time of surgical excision, particularly in patients with deep infiltrating advanced rhinophyma as in our case, with the presence of a neoplasm, complete layer excision of rhinophyma fibrous variant may be preferable and could be better to get more decent results in terms of cosmetics and recurrence.…”
Section: Discussionmentioning
confidence: 88%
“…Laser treatment takes more time, is more complicated, requiring expensive equipment, greater outlay, and the treatment results are comparable with other methods [32]. Rex et al, using the method of laser and electroresection, observed similar efficacy of the two of them, at a much lower cost of electrocautery [46].…”
Section: Discussionmentioning
confidence: 91%